Artificial intelligence and additive manufacturing for resilient supply chain in Africa: A systematic literature review - James Adu Peprah; John Amoah; Kofi Kwarteng; Abdul Bashiru Jibril; Taimur Sharif (Future Business Journal)
Abstract This study conducts a comprehensive literature review to explore the impact of artificial intelligence (AI) and additive manufacturing (AM) on supply chain resilience, with a particular focus on the African context. Drawing from literature published between 2013 and 2023 in the Web of Science database, our study reveals a substantial upward trend in related publications, peaking at 809 articles in 2022. Notably, Egypt emerged as the leading contributor to this field, highlighting its significant role in advancing research on AI and AM technologies. The findings demonstrate that these technologies are increasingly recognized as crucial enablers for enhancing supply chain resilience through improved predictive modeling, reduced lead times, and optimized inventory management. The implications of this study extend to policymakers and industry practitioners, suggesting that fostering the adoption of AI and AM can yield considerable economic and societal benefits. Our analysis underscores the necessity for further interdisciplinary collaboration and longitudinal studies to understand the long-term effects of these technologies on supply chain dynamics in Africa, thus offering valuable insights for future research and practice.